127k views
3 votes
Two astronauts, each with a mass of 50 kg, are connected by a 7 m massless rope. Initially they are rotating around their center of mass with an angular velocity of 0.5 rad/s. One of the astronauts then pulls on the rope shortening the distance between the two astronauts to 4 m. What was the averageangular speed exerted by the astronaut on the rope?

1 Answer

3 votes

Answer:

The angular velocity is
w_f = 1.531 \ rad/ s

Step-by-step explanation:

From the question we are told that

The mass of each astronauts is
m = 50 \ kg

The initial distance between the two astronauts
d_i = 7 \ m

Generally the radius is mathematically represented as
r_i = (d_i)/(2) = (7)/(2) = 3.5 \ m

The initial angular velocity is
w_1 = 0.5 \ rad /s

The distance between the two astronauts after the rope is pulled is
d_f = 4 \ m

Generally the radius is mathematically represented as
r_f = (d_f)/(2) = (4)/(2) = 2\ m

Generally from the law of angular momentum conservation we have that


I_(k_1) w_(k_1)+ I_(p_1) w_(p_1) = I_(k_2) w_(k_2)+ I_(p_2) w_(p_2)

Here
I_(k_1 ) is the initial moment of inertia of the first astronauts which is equal to
I_(p_1) the initial moment of inertia of the second astronauts So


I_(k_1) = I_(p_1 ) = m * r_i^2

Also
w_(k_1 ) is the initial angular velocity of the first astronauts which is equal to
w_(p_1) the initial angular velocity of the second astronauts So


w_(k_1) =w_(p_1 ) = w_1

Here
I_(k_2 ) is the final moment of inertia of the first astronauts which is equal to
I_(p_2) the final moment of inertia of the second astronauts So


I_(k_2) = I_(p_2) = m * r_f^2

Also
w_(k_2 ) is the final angular velocity of the first astronauts which is equal to
w_(p_2) the final angular velocity of the second astronauts So


w_(k_2) =w_(p_2 ) = w_2

So


mr_i^2 w_1 + mr_i^2 w_1 = mr_f^2 w_2 + mr_f^2 w_2

=>
2 mr_i^2 w_1 = 2 mr_f^2 w_2

=>
w_f = (2 * m * r_i^2 w_1)/(2 * m * r_f^2 )

=>
w_f = (3.5^2 * 0.5)/( 2^2 )

=>
w_f = 1.531 \ rad/ s

User Wauna
by
5.2k points